2011
DOI: 10.2139/ssrn.968091
|View full text |Cite
|
Sign up to set email alerts
|

Which Parametric Model for Conditional Skewness?

Abstract: Provided in Cooperation with:Bank of Canada, Ottawa Suggested Citation: Feunou, Bruno; Jahan-Parvar, Mohammad R.; Tédongap, Roméo (2013) AbstractThis paper addresses an existing gap in the developing literature on conditional skewness. We develop a simple procedure to evaluate parametric conditional skewness models. This procedure is based on regressing the realized skewness measures on model-implied conditional skewness values. We find that an asymmetric GARCH-type specification on shape parameters with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Thus, if RSV t+1 < 0 the distribution is left-skewed, and when RSV t+1 > 0 it is right-skewed. A theoretical justification for using RSV t+1 as a measure of skewness can be found in Feunou et al (2016). To provide more intuition on the behavior of RSV t+1 , we combine the previous asymptotic results to get…”
Section: Separating Downside From Upside Volatility: Theoretical Argumentioning
confidence: 99%
“…Thus, if RSV t+1 < 0 the distribution is left-skewed, and when RSV t+1 > 0 it is right-skewed. A theoretical justification for using RSV t+1 as a measure of skewness can be found in Feunou et al (2016). To provide more intuition on the behavior of RSV t+1 , we combine the previous asymptotic results to get…”
Section: Separating Downside From Upside Volatility: Theoretical Argumentioning
confidence: 99%
“…They find that signed jump variation, which they define as the difference between good and bad realized variance, is significantly related to expected stock returns. We notice that the relative signed jump variation considered by Bollerslev et al (2017) is a measure of skewness, as demonstrated by Feunou et al (2016). In that sense, Bollerslev et al (2017) are analyzing implications of individual firms' skewness for the cross-section of expected stock returns.…”
Section: Introductionmentioning
confidence: 85%
“…For example, Markowitz (1959) advocates the use of the downside semi-variance (namely, bad variance) as the measure of stock risk instead of the total variance, since the total variance also accounts for the upside semi-variance (namely, good variance) which measures not the risk but the potential of a stock. More recently, Feunou et al (2013), Bekaert et al (2015) and Segal et al (2015) find that expected excess returns on stocks are positively related to bad variance while they are negatively related to good variance. This suggests that, on the one hand, risk-averse investors are averse to increases in bad variance.…”
Section: Variance Risk Premium: Decomposition and Interpretationmentioning
confidence: 99%
See 2 more Smart Citations